2022
DOI: 10.3390/cells11233905
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide m6A Mapping Uncovers Dynamic Changes in the m6A Epitranscriptome of Cisplatin-Treated Apoptotic HeLa Cells

Abstract: Cisplatin (CP), which is a conventional cancer chemotherapeutic drug, induces apoptosis by modulating a diverse array of gene regulatory mechanisms. However, cisplatin-mediated changes in the m6A methylome are unknown. We employed an m6A miCLIP-seq approach to investigate the effect of m6A methylation marks under cisplatin-mediated apoptotic conditions on HeLa cells. Our high-resolution approach revealed numerous m6A marks on 972 target mRNAs with an enrichment on 132 apoptotic mRNAs. We tracked the fate of di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…Our analyses revealed that METTL3 knockdown perturbs the polysomal association of PAWR, IFI6, and TP53INP1, the nonpolysomal (mRNP or monosome) association of IFI6, GADD45B, HRK, BMF, and BCL2A1, without any major effects on the translation efficiency of PHLDA1 and CARD14 (Figure S2). To interrogate the polysomal association of the apoptotic candidate transcripts in the presence or absence of TNF-α in METTL3 knockdown cells, we performed polysome profiling analyses with HeLa cells as previously reported (Alasar et al, 2022). TNF-α treatment did not change the polysome profile of METTL3 knockdown cells compared to the control CHX-treated cells (Figure 4a).…”
Section: Tnf-α-mediated Translational Efficiency Of Mrnas Is Modulate...mentioning
confidence: 78%
See 3 more Smart Citations
“…Our analyses revealed that METTL3 knockdown perturbs the polysomal association of PAWR, IFI6, and TP53INP1, the nonpolysomal (mRNP or monosome) association of IFI6, GADD45B, HRK, BMF, and BCL2A1, without any major effects on the translation efficiency of PHLDA1 and CARD14 (Figure S2). To interrogate the polysomal association of the apoptotic candidate transcripts in the presence or absence of TNF-α in METTL3 knockdown cells, we performed polysome profiling analyses with HeLa cells as previously reported (Alasar et al, 2022). TNF-α treatment did not change the polysome profile of METTL3 knockdown cells compared to the control CHX-treated cells (Figure 4a).…”
Section: Tnf-α-mediated Translational Efficiency Of Mrnas Is Modulate...mentioning
confidence: 78%
“…qPCR and western blot analyses revealed changes in the expression of writers (Figure 1). Similarly, treatment of HeLa cells with CP downregulates the expression of METTL3 and METTL14 (Alasar et al, 2022), suggesting that downregulation of writer proteins may be a common feature in apoptotic cells independent of the inducers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…YTHDF1 can affect the progression of ovarian, breast and small cell lung cancers, and it can drive hypoxia-induced autophagy in hepatocellular carcinoma, but no relevant studies have been reported on BLCA [ 15 , 16 , 17 , 18 ]. Decreased METTL3 expression increased the sensitivity of Hela cells to cisplatin, and increased METTL3 expression in bladder cancer cells increased the resistance of bladder cancer cells to cisplatin [ 12 , 19 ]. In m6A modification, the writer plays different roles by binding to different readers, so we explored the effects of the writer METTL3 and the reader YTHDF1 on BLCA cell proliferation and cisplatin sensitivity [ 14 , 20 , 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%